Recombinant orthopoxvirus primes colon cancer for checkpoint inhibitor and cross-primes T cells for anti-tumor and anti-viral immunity - Kim, Sang-In (Mol Cancer Ther, 2020)
While it is known that oncolytic viruses can inflame and recruit immune cells to otherwise immunosuppressed tumor microenvironments, the influence of the anti-viral immune response on anti-tumor immunity is less clear across viral platforms and tumor types. CF33 is a recombinant orthopoxvirus backbone effective against colon cancer. We tested derivatives of CF33 with and without immune checkpoint inhibition (anti-PD-L1) in mouse models of colon cancer. Results showed that the efficacy of CF33 backbone with J2R deletion (single-deleted) against colon cancer is not altered by additional deletion of F14.5L in vitro or in vivo. CF33 infection upregulated PD-L1 expression on tumor cells and led to an increased influx of lymphocytes and macrophages in tumors. Also, the levels of active CD8+ (IFNγ+) T cells in the virus-treated tumors were higher than those in control-treated tumors. Furthermore, a combination of CF33-derivatives with anti-PD-L1 resulted in durable tumor regression and long-term survival, resistant to tumor rechallenge. Analysis of immune cells from the treated mice showed that tumor-specific T cell activation occurred more robustly in tumors treated with the virus and that T cells were more strongly activated against the virus than against tumor, in an MHC-I dependent manner. Our findings warrant further studies on the role of cross-priming of T cells against viral and tumor antigens, in the overall success of viroimmunotherapy.